Flushing affects secretion of the hormones controlling reproduction - Rhodes, M.T.; Minton, J. Ernest; Stevenson, Jeffrey S.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nineteen gilts were assigned to receive either 0 or 15 mg altrenogest/day for 14 consecutive days. On the day corresponding to the last altrenogest treatment, gilts not fed altrenogest were injected twice (morning and evening) with prostaglandin F2 a to ensure regression of their corpora lutea. From the ninth day of altrenogest treatment until estrus, one-half of each altrenogest group was offered an additional 3.4 lb of ground sorghum grain (flush). Serial blood samples were collected for a 4-h period each day from day 1 through day 4 (last altrenogest or prostaglandin F a treatment was day 0) and analyzed for estradiol-1713 progesterone follicle-stimulating hormone (F SH) and luteinizing hormone (LH). Flushing resulted in an increased ovulation rate (16.3 vs 13 corpora lutea) and a shortened interval to estrus (5 vs 5.9 days). Altrenogest treatment resulted in an increased interval to estrus (5.8 vs 5.1 days). The data were analyzed relative to estrus using days -5, -4, -3 and -2 before first standing estrus (day 0). Altrenogest increased estradiol by 1.5 pg/ml and decreased progesterone by .9 ng/ml, whereas flushing increased (P<.05) progesterone by .6 ng/ml and concentration of FSH by 1.6 ng/ml. These data point to changes in FSH and(or) P as likely hormonal causes for increased ovulation rates in flushed gilts.
Keywords: Swine; Hormones; Reproduction